A Cross Sectional Study on the Safety and Efficacy of Distal Trans-Radial Access (DTRA) for Coronary Intervention in Individuals with Low BMI - Muhammad Ijaz Khan, Shireen Shah, Yasir Saood, Aftab Alam Tanoli, Talal Wasif Mirza, Vickee Kumar Mamtani (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: The research aimed for examining the safety and effectiveness of distal trans-radial access (dTRA), a new coronary intervention procedure, in individuals with low BMI. Methods: The design of this study was a cross sectional study design. This study was conducted at Mayo Hospital Lahore and the duration of this study was from December 2020 to December 2022. The participants of this study was 67 patients who had a coronary intervention. The patients were divided into two groups: 38 patients had traditional trans-radial access (cTRA) and 29 patients got direct trans-radial access (dTRA). Results: The research outcomes indicated that the success rates for puncture procedures in both groups, dTRA and cTRA, were not significantly different. Specifically, the success rate for dTRA was found to be 96.6% while cTRA recorded a success rate of 97.4%. This difference was not considered to be statistically significant as the p-value was 0.846, which means there was an 84.6% chance that the results were due to random chance and not a true difference between the groups. This indicates that both dTRA and cTRA are effective in puncture procedures and can produce similar results in terms of success rate. It is crucial to consider these results alongside the limitations of the research. Despite the overall results indicating a similar success rate between the two groups, there was a disparity in success rates for single-needle puncture procedures. In this aspect, the cTRA group outperformed the dTRA group with a success rate of 81.6% compared to 51.7% for the dTRA group. This difference was statistically significant with a p-value of 0.020, indicating that the results were not due to random chance. However, the dTRA group did have some advantages over the cTRA group. The compression hemostasis time, the time required for the bleeding to stop, was faster for the dTRA group, with a p-value of 0.01. Additionally, the incidence of radial artery occlusion was less frequent in the dTRA group compared to the cTRA group, with a p-value of 0.007 (4% compared to 33.3% in the cTRA group). Practical Implication: The study examines the first-time use of dTRA in low BMI people and looks at efficacy and safety. With a success rate of 96.6% in the dTRA group and a success rate of 97.4% in the control group (cTRA), the puncture success rate was found to be comparable between the two groups. The success rate was lower in the dTRA group compared to the cTRA group, and it took them longer to penetrate the skin with a single needle. The two groups’ puncture-related side effects, such as bleeding and hematoma, were not significantly different from one another. Even though the dTRA group’s patients reported more comfort, the dTRA group’s compression hemostasis time and Visual Analog Scale (VAS) ratings were lower. Conclusion: The research shows that in individuals with low BMI, coronary intervention with dTRA is both secure and efficient. This approach offers a less complicated, more effective, and efficient alternative to conventional trans-radial access. Keywords: Conventional Trans-Radial Access, Body Mass Index, Percutaneous Coronary Intervention, Bleeding, Puncture